Bio-Induksi Ranting Cabang Gaharu (Gyrinops versteegii) Di Perkebunan Gaharu Desa Pejaring Lombok Timur - I Gde Adi Suryawan Wangiyana; Efendi Iskandar (ULIN: Jurnal Hutan Tropis, 2021)
Bio-induction on the branch of agarwood tree (Gyrinops versteegii) is a good alternative method to increase resin productivity. The aim of this research is to applied bio-induction on the branch of G. versteegii with different diameters. Different branch diameter was the treatment on this research including branch 1 (diameter 70 mm ± 5 mm), branch 2 (85 mm ± mm), branch 3 (100 mm ± mm). Fusarium solani isolate of Institute for Technology Research and Development of Non-Timber Forest Product was used as a bio-induction agent. This isolate was cultured on bean sprout broth media for 28 days. Bio-induction was carried using standard procedure developed by Forest Research and Development Agency. Observation of the result conducted 3 months after bio-induction. There were 3 parameters of bio-induction result including resin area production, discoloration in form of browning on branch, and fragrance level of resin. Branch 2 has the largest resin area production. However, branch 3 has the highest score of browning and fragrance level. This result indicated a correlation between browning on branch and fragrance level quality. It could be concluded that bio-induction on larger branch diameter could produce higher productivity of resin, especially on browning and fragrance level parameter